Myth Conceptions of Academic Work - Johnston, Ian C. (Canadian Journal of Higher Education, 1991)
The creation of the new university-colleges in British Columbia provides an opportunity for a reassessment of the professor’s workload. How relevant are research and publication to the quality of undergraduate instruction? Universities have traditionally maintained that such research and publication are essential to excellent teaching. However, research studies for many years have consistently revealed that such a claim has no apparent basis in fact, and a number of other commentators have complained about the deleterious effect of research and publication on instruction. Thus, in the new university-colleges the instructors’ workloads should not be based upon the models common in universities.